Early outcomes of the “Chimney” commando procedure in the small aortic and mitral annuli - Yang, Mingyuan; Liu, Wenhao; Song, Laichun; Wu, Jingcheng; Xiao, Yong; Liu, Yuhang; Tao, Liang (Frontiers in Cardiovascular Medicine, 2023)
Objective. Combined aortic and mitral valve replacement with reconstruction of the intervalvular fibrous (The Commando procedure) in patients with small aortic and mitral annuli is a technical challenge. In this study, we evaluate the safety and early outcomes of the ‘‘Chimney’’ Commando procedure using a self-assembled valve composite graft in patients with small aortic and mitral annuli after prior valve surgery. Methods. From April 2021 to April 2022, 30 consecutive cases of the ‘‘Chimney’’ Commando procedure with a self-assembled valve composite graft and other combined cardiac procedures were performed completely for re-operative patients with small aortic roots. Data were obtained through a medical record review, at Asian Heart Hospital Wuhan. Results. Patient mean age was (52.7±13.53) years; 93.3% were female, and all had previous heart valve surgery, of which 90% had double valve replacement (DVR). Hospital death occurred in 3.3% (n = 1) of patients due to malignant arrhythmias and multiorgan failure. Postoperative echocardiogram showed the size of the aortic valve prosthesis and mitral valve prosthesis was 24.23±1.60 mm and 28.33±1.21 mm, respectively. Intact IVF reconstruction was conﬁrmed in all patients with no abnormal communication between the left heart chambers. There were no major postoperative complications, including operative mortality, renal failure requiring permanent dialysis, mediastinitis, except for 1 postoperative sick sinus syndrome and 1 re-sternotomy for bleeding. Echocardiography in the sixth month showed the peak gradient of the aortic valve and mitral valve was 17.60±5.94 mmHg and 12.80±4.90 mmHg, respectively. Conclusions. Compared to the Commando operation, the early outcomes and safety of the "Chimney" Commando procedure proved to be a feasible therapy option for patients with small aortic and mitral annuli after prior valve operations, permitting enlargement of aortic and mitral annuli and implantation of the desired valve prosthesis.